2009
DOI: 10.1080/01904160903092663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potassium Application on Flavor Compounds of Cherry Tomato Fruits

Abstract: A pot experiment was conducted to determine the effects of potassium (K) application on volatile compounds, taste compounds, and firmness of fresh tomato fruits. Each pot was filled with 8 kg of clean sand. The experiment consisted of six K application rates with 0, 1.25, 2.5, 5.0, 10.0, and 20.0 mmol K L −1 in the nutrient solution. Volatile compounds, soluble sugars, soluble solids, titratable acidity, and firmness of fresh tomato fruits were measured. The results show that the concentrations of 3-methylbuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
(45 reference statements)
1
13
0
1
Order By: Relevance
“…There were highly significant differences ( P < 0.01) among tomato accessions for overall flavour and flavour-contributing components except for herbaceous odour, herbaceous flavour and salty taste (Table 2). Fruit firmness is claimed to be associated with fruit flavour (Magee et al , 2003; Wang et al , 2009). For that reason, firmness was measured in this core collection and average firmness was found to be 10.9 N, ranging widely from 5.8 to 35.8 N. Extremely soft (low firmness) accessions were PI 128129, Tomate, M7281 and Tomate del Lugar, whereas those with a high level of firmness were 888, Castle Rock and Sun1643.…”
Section: Resultsmentioning
confidence: 99%
“…There were highly significant differences ( P < 0.01) among tomato accessions for overall flavour and flavour-contributing components except for herbaceous odour, herbaceous flavour and salty taste (Table 2). Fruit firmness is claimed to be associated with fruit flavour (Magee et al , 2003; Wang et al , 2009). For that reason, firmness was measured in this core collection and average firmness was found to be 10.9 N, ranging widely from 5.8 to 35.8 N. Extremely soft (low firmness) accessions were PI 128129, Tomate, M7281 and Tomate del Lugar, whereas those with a high level of firmness were 888, Castle Rock and Sun1643.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, K concentrations in soilless culture systems should be managed to supply sufficient leaf K to achieve high yield, while avoiding Mg uptake suppression due to excessive K. Moreover, the plant yield and quality are closely related to plant growth media, which could influence the nutrient supply concentrations in solution [29]. Wang et al (2009) reported that higher yields were obtained when solution K concentration was at 2.5-5 mM for cherry tomato growing in plastic pots filled with sand [56]. Hao and Papadopoulos (2003) applied 10 mM K in the nutrient solution for greenhouse tomato crop grown on rockwool [4].…”
Section: Mg and K Management In Soilless Vegetable Productionmentioning
confidence: 99%
“…Kalium memiliki peran utama terhadap faktor nutrisi buah. Kandungan kalium yang tersedia bagi tanaman akan mempengaruhi konsentrasi total asam tertitrasi pada buah, karena tanaman juga meningkatkan produksi asam-asam organik (Wang et al, 2009). Kalium memiliki peran terhadap proses fotosintesis, akumulasi karbohidrat, dan asam organik yang mendukung pertumbuhan dan fungsi tanaman (Huang dan Snapp, 2009).…”
Section: Hasil Dan Pembahasan Interaksi Genotipe × Kno3unclassified